Assessing the potential impacts of urban expansion on regional carbon storage by linking the LUSD-urban and InVEST models. (January 2016) - He, Chunyang; Zhang, Da; Huang, Qingxu; Zhao, Yuanyuan
Abstract: The timely and effective assessment of the impacts of urban expansion on regional carbon storage is an important issue in the fields of urban ecology and sustainability science. This study used a new model to assess the impacts of urban expansion on regional carbon storage by linking the LUSD-urban and InVEST models. First, the LUSD-urban model was used to simulate urban expansion. Then, the InVEST model was adopted to assess the impacts on regional carbon storage. The linked model combines the strengths of these two models. Not only can it simulate and project the process of urban expansion but it can also assess the impacts of urban expansion on regional carbon storage. A case study in Beijing showed that the relative error between the simulated carbon storage loss and the actual loss was less than 12%. We argue that the linked model can be applied to assess the ecological effects of future urban expansion. Highlights: We developed a model to assess the impacts of urban expansion on carbon storage. The linked model combines the strengths of the LUSD-urban and the InVEST model. The potential impacts of future urban expansion on carbon storage can be estimated. A case study in Beijing confirms that the model is relatively efficient and accurate.